P108 Cytosponge in the real-world: triage of Barrett's surveillance and reflux in a single non-specialist hospital. (19th June 2022) - Morris, Danielle; Shaw, Kim; Cole, Francoise; Baker, Pearl; Ebon, Martin; Evans, James
Abstract : Introduction: During the COVID-19 pandemic gastroscopy was halted with large burden on recovery and risk of late diagnosis. We established an early diagnosis service using Cytosponge to triage patients to timely gastroscopy and management Methods: 2 patient cohorts were used: 1. Barrett's oesophagus (BO) on endoscopic surveillance 2. Patients with symptoms of gastro-oesophageal reflux referred for routine gastroscopy. Exclusions were patients with dysplasia on last gastroscopy, fundoplication, pregnancy and patient preference. Triage of patients on the waiting list was from endoscopy referrals, Barrett's surveillance database and telephone triage. 2 research nurses and 2 clinical nurse specialists were trained in delivering Cytosponge. A patient satisfaction survey was completed. All cytology specimens were analysed by Cyted. Results were relayed to patients within 4 weeks by consultant led nurse-run teleclinic and letter. Clinical triage was according to the table below. TFF3+ was used as a marker for intestinal metaplasia (IM), P53+ve and atypia for potential dysplastic change. Results: 470 patients agreed to Cytosponge over 14 months November 2020-January 2022. 22 cancelled-mostly COVID related. 34 failed to swallow (5.5% of Barrett's, 8.9% reflux). of those successfully swallowing the sponge 6% were inadequate samples in Barrett's and 9% reflux. No major adverse events occurred. Conclusion: We report on the largest single site series of Cytosponge in non-specialist clinical practice in England and its pragmatic use in patients management and pandemic recovery. Significant benefits in the Barrett's cohort were timely identification of dysplasia and those longer requiring surveillance. Benefits in the reflux group include identification of new BO, avoiding unnecessary gastroscopy and early discharge. Overall reduced endoscopy resulted in reduced cost, lower carbon footprint and improved patient experience. Careful follow up and longer-term outcomes will provide confidence to continue this new technique in routine clinical practice.